2013
DOI: 10.1179/1476830513y.0000000053
|View full text |Cite
|
Sign up to set email alerts
|

Asparagus racemosusmodulates the hypothalamic–pituitary–adrenal axis and brain monoaminergic systems in rats

Abstract: MAR showed a physiological modulation of the stress pathways. Interestingly, in most brain regions the change in monoaminergic systems was limited by a ceiling effect at a dose of 100 mg/kg. These observations could explain the traditional use of AR as an adaptogen and a functional food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…It is demonstrated that hypercorticosteronemia is observed in both T2DM and stress conditions and also in their cooccurring situation [7, 6466], a result of overactivation of hypothalamic-pituitary-adrenal cortex- (HPA-) axis function [67]. Similar to earlier observations, there was significant increase in the level of corticosterone in the plasma in cooccurring T2DM and stress exposed animals in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…It is demonstrated that hypercorticosteronemia is observed in both T2DM and stress conditions and also in their cooccurring situation [7, 6466], a result of overactivation of hypothalamic-pituitary-adrenal cortex- (HPA-) axis function [67]. Similar to earlier observations, there was significant increase in the level of corticosterone in the plasma in cooccurring T2DM and stress exposed animals in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…Monoamines can regulate the HPA-axis activity (Fukudo et al, 1992;Krishnamurthy et al, 2013). They are altered in different brain regions such as hippocampus, hypothalamus, PFC, and amygdala in both stress and IBS conditions p50.05 compared with RS+OÀ4 (one-way ANOVA followed by the Student Newman-Keuls test).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that AR is frequently used in foods and nutraceuticals.Its effectiveness has only been studied in relation to experimental disorders. Its goal was to determine the impact of standardised AR methanolic extract (MAR) on experimentally unaltered animals in order to determine the effects on stress pathways [23].…”
Section: Asparagus Racemosusmentioning
confidence: 99%